2021
DOI: 10.1038/s41467-020-20523-3
|View full text |Cite
|
Sign up to set email alerts
|

PKA drives an increase in AMPA receptor unitary conductance during LTP in the hippocampus

Abstract: Long-term potentiation (LTP) at hippocampal CA1 synapses can be expressed by an increase either in the number (N) of AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazole propionic acid) receptors or in their single channel conductance (γ). Here, we have established how these distinct synaptic processes contribute to the expression of LTP in hippocampal slices obtained from young adult rodents. LTP induced by compressed theta burst stimulation (TBS), with a 10 s inter-episode interval, involves purely an increase in N … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(48 citation statements)
references
References 65 publications
7
41
0
Order By: Relevance
“…Unlike what was previously observed in mice (Gong et al, 2009), upon blockade of GAT1 transporters with SKF89976a (5M), LTP induction with mild TBS (5x4) caused a long-lasting enhancement of 40.6±2.9% (n=6, Fig. 2 It is generally accepted the expression of LTP relies on the Ca 2+ -dependent activation and consequent auto-phosphorylation of CaMKII, that then elicits the recruitment of AMPA GluA1 subunits (Appleby et al, 2011;Park et al, 2021). However, it has been reported that this is not required for the expression of NMDA-dependent LTP in different hippocampal subfields in the mouse (Cooke et al, 2006).…”
Section: Resultsmentioning
confidence: 69%
See 2 more Smart Citations
“…Unlike what was previously observed in mice (Gong et al, 2009), upon blockade of GAT1 transporters with SKF89976a (5M), LTP induction with mild TBS (5x4) caused a long-lasting enhancement of 40.6±2.9% (n=6, Fig. 2 It is generally accepted the expression of LTP relies on the Ca 2+ -dependent activation and consequent auto-phosphorylation of CaMKII, that then elicits the recruitment of AMPA GluA1 subunits (Appleby et al, 2011;Park et al, 2021). However, it has been reported that this is not required for the expression of NMDA-dependent LTP in different hippocampal subfields in the mouse (Cooke et al, 2006).…”
Section: Resultsmentioning
confidence: 69%
“…3.D, P>0.05). Expression of late-LTP induced by moderate TBS (15x4) in C57BL/6J mice is dependent on PKA activity and protein synthesis (Nguyen and Kandel, 1997), yet only multiple spaced TBS trains have been described to induce an LTP dependent on PKA in hippocampal slices from Sprague-Dawley rats (Park et al, 2016(Park et al, , 2021. To confirm this, we readdressed the PKA-dependency of TBS induced LTP by using a moderate TBS (15x4), as used by Nguyen and Kandel in 1997 and a strong TBS 3x(15x4) separated by 6 min, that would assure the conditions of three TBS bursts with sufficient spacing to mimic the spaced TBS used by Park et al (2016), and in rats of similar age to the ones in the mouse study (12 weeks).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since CP-AMPARs are only transiently inserted into these synapses, with a dwell time in the order of minutes [19], we previously hypothesized [20] and then demonstrated [18] that these receptors could serve to "tag" synapses for enhanced LTP. Our data support a model whereby the sTBS initiates local de novo protein synthesis by leading to the transient insertion of CP-AMPARs in a two-step process that requires, firstly, the insertion of these receptors at perisynaptic sites and, secondly, their movement into the synapse [17].…”
Section: Discussionmentioning
confidence: 99%
“…In summary, we can conclude that CP-AMPARs are an integral part of a form of heterosynaptic metaplasticity that is commonly referred to as the STC process. CP-AMPARs are inserted into the synapse in two stages, firstly via an NMDAR-triggered PKA-dependent insertion into perisynaptic sites and then by an NMDARtriggered CaMKII-dependent movement into the synapse [19]. The former provides many opportunities for modulation via neurotransmitters and other factors that regulate cAMP levels in neurons.…”
Section: Discussionmentioning
confidence: 99%